(untitled) (Journal of Computational Mathematics, 2018)
A new derivation is given for the Quotient Singular value Decomposition (QSVD) of matrix pair (A,B) having the same number of columns. Certain properties of the quotient singular values are proved. The relation between the QSVD and the SVD is analyzed in some detail.